Answer: Translation
The difference between the first equation and the second is that the second is moved one space higher. All of its points will be a unit higher than the other. Because of this change in height, the name of the transformation is a translation
Hope this helps comment below for more questions :)
Answer:
f(- 2) = - 2
Step-by-step explanation:
To evaluate f(- 2) substitute x = - 2 into f(x)
f(- 2) = 3(- 2) + 4 = - 6 + 4 = - 2
Answer:
Step-by-step explanation: how do u supposed to divide that???
Answer:
The correct answer would be 2π x 2²/5
Step-by-step explanation:
First, calculate the product, and evaluate the power which would be 2³π/5 and the solution is in an alternate form, therefore making it rational. :)
Answer:
(-3x²- 9x+5) - (-2x²-4x +7)
= (-3x²- 9x²+5) (2x²+4x +7)
=-3x²-9x+5+2x²+4x-7
=-3x²+2x²-9x+4x+5-7
=-x²-5x-2